Potensi Senyawa Timokuinon, Timol, dan Karvakrol dari Jintan Hitam (Nigella sativa) sebagai Agen Antibakteri Alami dalam Keamanan Pangan: Analisis In Silico terhadap Escherichia coli dan Salmonella - Zuhroh, Nadiyah; Rasmiyana, Rasmiyana; Rachmawati, Yulia (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
This study aims to evaluate the potential of active compounds from black seed (Nigella sativa), namely thymoquinone, thymol, and carvacrol, as natural antibacterial agents in food safety against pathogenic bacteria Escherichia coli and Salmonella typhi. The molecular docking method was used to analyze the interactions between these compounds and bacterial target proteins, namely GyraseB in E. coli and LsrB in S. typhi. The results showed that all three compounds were able to bind to the target proteins through hydrogen, hydrophobic, and electrostatic interactions. Carvacrol exhibited the strongest binding energy (-177.5 Kcal/mol) against E. coli, while thymoquinone showed the strongest binding energy (-186.0 Kcal/mol) against S. typhi. Furthermore, this study revealed the potential of these ligands to inhibit resistant Salmonella typhi, suggesting their possible use in addressing bacterial resistance issues in food contamination. These findings still require further in vitro and in vivo investigation. This research provides important insights for the development of natural antibacterial agents in the food industry, particularly in preventing contamination by pathogenic bacteria and enhancing food safety